Childcare arrangements and the role of childcare policy provisions in Romania - Kovacs, B (2014)
The focus of the thesis is the exploration of young children’s routine childcare arrangements and the role played by childcare policy provisions (in cash, in time and in kind, through services) in shaping these arrangements in the Romanian context. Through the narratives of 68 family carers in 37 urban and rural Romanian households in multi-ethnic Transylvania, the study investigates the household level processes whereby young children’s care arrangements come to be and explores the ways in which the design of and access to childcare policy provisions might shape young children’s routine care arrangements. In doing so, the thesis reconceptualises the term childcare arrangements and provides a descriptive account of ten different routine arrangements for the care of young children. Through an inductive analysis of carer narratives, the thesis also develops a heuristic tool – hierarchies of care ideals – that lies at the heart of a refined explanatory framework pertaining to the conception and implementation of individual care arrangements. This framework complements existing analytic models that have been developed to explain mothers’ employment and care related decisions during their children’s early years. Building on this inductively developed framework, the thesis expands on the role that different childcare policy provisions were said to play in shaping households’ childcare choices. The thesis reveals that the designs of policy provisions and households’ access to different benefits directly shape young children’s care arrangements. Furthermore, through the analysis of narrative pairs available for most households in the study, the thesis explores the gendered ways in which mothers and fathers narratively constructed agency in relation to decision-making about children’s care arrangements. Finally, the thesis proposes three real-type decision-making models described by carers in the study, revealing the dynamic nature of household decision-making in relation to children’s care arrangements.